2019
DOI: 10.1136/bmjopen-2019-030513
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood circulating vitamin D and colorectal cancer risk in Asian countries: a systematic review and dose-response meta-analysis

Abstract: ObjectivesTo assess the association between blood circulating vitamin D levels and colorectal cancer risk in the Asian population.DesignThis is a systematic review and dose-response meta-analysis of observational studies that investigated the relationship between blood circulating vitamin D levels and colorectal cancer risk in the Asian population.Data sourcesRelevant studies were identified through a literature search in Medline, Embase and Web of Science from 1st January 1980 to 31st January 2019. Eligibilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…We found 35 meta‐analyses that investigated relationships between vitamin D status, as measured by circulating 25OHD and cancer outcomes: 29 on cancer incidence, ( 5,6,11,14,29–53 ) 3 on cancer mortality, (10,54,55 ) and 3 on both ( 13,56,57 ) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We found 35 meta‐analyses that investigated relationships between vitamin D status, as measured by circulating 25OHD and cancer outcomes: 29 on cancer incidence, ( 5,6,11,14,29–53 ) 3 on cancer mortality, (10,54,55 ) and 3 on both ( 13,56,57 ) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Holiday sun exposure before melanoma diagnosis has been reported to be associated with lower thickness and the exposure after melanoma diagnosis was also associated with reduce melanoma recurrence 101 . Furthermore, increasing evidence has been suggested that circulating levels of vitamin D may play a protective role against several types of cancer such a bladder 102 and colorectal 103 . Also, a recent pooled analysis of two randomized controlled trials (RCTs) and a prospective cohort found that higher 25(OH)D levels were inversely associated with breast cancer risk with levels ≥ 60 ng/ml ((≥ 150 nmol/L) being most protective 104 .…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer, particularly in late stages, is associated with vitamin D deficiency [56,[66][67][68][69], also related to 1α-hydroxylase downregulated expression, which is strongly correlated with cancer severity [95] whereas higher circulating levels of 25(OH)D are associated with a decreased risk of colorectal cancer in both Asian (OR: 0.75; 95% CI: 0.58 to 0.97; p = 0.034) [70] and Western populations (p = 0.041) [71].…”
Section: Vitamin D and Cancer: Epidemiological Evidencementioning
confidence: 99%
“…Several observational studies have shown that circulating levels of 25(OH)D, used as surrogate marker for the evaluation of vitamin D status, may be associated with cancer risk [ 5 , 6 , 56 , 57 , 58 , 59 ] and prognosis [ 6 , 60 , 61 , 62 , 63 , 64 , 65 ]. A strong association between low 25(OH)D circulating levels and colorectal [ 6 , 56 , 60 , 61 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], prostate [ 59 , 62 , 63 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ] and breast [ 52 , 58 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ] cancer risk has been reported.…”
Section: Vitamin D and Cancer: Epidemiological Evidencementioning
confidence: 99%